MIKROBIOLOGICAL TESTING OF CAROTENOID PIGMENT EXTRACT AGAINST THE PATHOGENIC BACTERIUM Vibrio harveyi IN SHRIMP PONDS - Karenina Azzahra; Yusni Ikhwan Siregar; Ummi Mardhiah Batubara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Shrimp is one of the key fishery commodities for the national economy. The main problem in shrimp farming is infection by the bacterium Vibrio harveyi, which is commonly controlled using conventional antibiotics. Uncontrolled antibiotic use can lead to bacterial resistance; therefore, it is necessary to identify alternative antibacterial compounds that are more environmentally friendly, such as carotenoid pigment extracts from marine microorganisms. This study aims to analyze the antibacterial activity and determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of carotenoid pigment extracts against V. harveyi. Carotenoid pigment analysis was performed using UV-Vis spectrophotometry, while antibacterial activity was tested using the disk diffusion method (Kirby-Bauer). MIC and MBC were determined using the liquid dilution and pour plate methods. The extract concentrations used were 12,5%, 25%, 50%, and 100%. The results showed that the extract exhibited a maximum absorbance at 490 nm, with a total carotenoid content of 14.56 µg/mL. In addition, the carotenoid pigment extract from isolate LD02 inhibited the growth of V. harveyi, with inhibition zones ranging from 1.41 to 3.58 mm. The MIC was 14.56 µg/mL, while the MBC was>14.56 µg/mL, indicating that the extract exhibits bacteriostatic activity against V. harveyi.